A simple and green analytical method for determination of copper(II) in whisky and sugarcane spirit by diffuse reflectance spectroscopy - Carlos De Souza, João [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Royal Society of Chemistry (RSC), 2016)
In this paper we propose a new, fast, simple, economical, portable and environmentally friendly analytical methodology for the determination of copper(II) ions in whisky and sugarcane spirit, using the combination of spot-test and diffuse reflectance spectroscopy. The method is based on the reflectance measurements at 559 nm, of the complex formed from the spot test reaction between the copper(II) ions with the chromogenic agent 1-(2-pyridylazo)-2-naphthol (PAN), using filter paper as the solid support. The best conditions for the reaction occurred with the addition of 30 μL of a PAN solution at a concentration rate of 0.12% m/v in ethanol and 30 μL of an alcoholic solution of copper(II) ions at 40.0% v/v with pH 5.00 and 5 minutes of reaction time. The following elements were found to interfere in the reaction process-iron(III), nickel(II), cobalt(II), cadmium(II), manganese(II), zinc(II) and lead(II) ions. Malonic acid and sodium triphosphate at a concentration of 0.25% m/v were therefore used as masking agents, which contributed towards the reduction of the magnitude of the interference effect from around 20.3% to approximately 2.0%. Under optimized conditions for the determination of copper(II), the analytical curve obtained could be described by: ΔAR = 0.0121CCu(II) + 0.0038 (R2 = 0.9982). Linearity was obtained up to a concentration of 10.0 mg L-1 of copper(II), and limits of detection and quantification (calculated using the standard deviation of the blank) were 0.12 and 0.47 mg L-1 of copper(II), respectively. The proposed method was applied for the determination of copper(II) ions in samples of whisky and sugarcane spirit and the results were compared with those obtained by the official method with a 95% level of confidence.